2021
DOI: 10.2147/ceg.s219556
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Antibiotic-Refractory Pouchitis: Management Challenges

Abstract: Background Pouchitis is the most common long-term complication in patients with ulcerative colitis who underwent restorative proctocolectomy with ileal pouch-anal anastomosis. The incidence of acute pouchitis is 20% after 1 year and up to 40% after 5 years. Chronic antibiotic-refractory pouchitis develops in approximately 10% of patients. Aim To present a narrative review of published literature regarding the management of chronic antibiotic-refractory pouchitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 100 publications
0
1
0
Order By: Relevance
“…Some of the main treatment options include antibiotics, immunomodulators, anti-tumor necrosis factor (anti-TNF), and even probiotics. Although requiring prolonged use of antibiotics, CARP has shown to be responsive in some studies to ciprofloxacin in combination with metronidazole [1,14]. In addition to antibiotics, an immunosuppressive approach has also proven successful in treating the inflammation associated with CARP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the main treatment options include antibiotics, immunomodulators, anti-tumor necrosis factor (anti-TNF), and even probiotics. Although requiring prolonged use of antibiotics, CARP has shown to be responsive in some studies to ciprofloxacin in combination with metronidazole [1,14]. In addition to antibiotics, an immunosuppressive approach has also proven successful in treating the inflammation associated with CARP.…”
Section: Discussionmentioning
confidence: 99%
“…The ileal pouch is a surgically implanted artificial pouch that functions to replace the colon. The pouch can be inflamed leading to CARP [1]. Patients with CARP frequently experience symptoms like diarrhea, rectal bleeding, abdominal pain, and a lower quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosing and managing pouchitis and identifying surgical failures are challenging tasks for physicians who care for these patients. 43 …”
Section: Gius and Transperineal Ultrasoundmentioning
confidence: 99%
“…Bismuth, bismuth carbomer, and alicaforsen enema in CARP treatment have reported conflicting results. 18,24 On the contrary, it was observed that topical tacrolimus and cyclosporine exhibited efficacy in cases of CARP. 20,25-27 • Biological agents are utilized as rescue therapy in CARP treatment for patients who do not respond to budesonide.…”
mentioning
confidence: 99%
“…Insufficient data exists to provide a definitive assessment of the efficacy of immunomodulators as an induction therapy for CARP, whether utilized independently or in conjunction with biologic agents. 6,20,24 However, they can be used as an option for remission maintenance. 20…”
mentioning
confidence: 99%